2005
DOI: 10.1002/chin.200521283
|View full text |Cite
|
Sign up to set email alerts
|

Proteases Universally Recognize β Strands in Their Active Sites

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 1 publication
0
32
0
1
Order By: Relevance
“…A review of a large number of proteases in the PDB database has revealed that proteases generally bind their substrates in an extended binding conformation, which is to a large degree defined by β-strand-type backbone interactions [32,33]. The PS-SCLs profile the primary selectivity in the S1-S4-binding pockets of a protease independently, without accounting for cross-talk between subsites and without the requirements for optimal alignment of the peptide backbone.…”
Section: Discussionmentioning
confidence: 99%
“…A review of a large number of proteases in the PDB database has revealed that proteases generally bind their substrates in an extended binding conformation, which is to a large degree defined by β-strand-type backbone interactions [32,33]. The PS-SCLs profile the primary selectivity in the S1-S4-binding pockets of a protease independently, without accounting for cross-talk between subsites and without the requirements for optimal alignment of the peptide backbone.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that when released from the triple-helical conformation, the cleavage site sequence in type I collagen has the propensity to form ␤-bend and ␤-strand structures (61). Protease active sites appear to accommodate ␤-strand structures universally (62). Besides liberating the N-terminal region of chain 1T for hydrolysis, the destabilization of the THP also causes a partial detachment of chain 3T near the THP C terminus (Fig.…”
Section: Molecular Mechanisms Of Collagen Catabolismmentioning
confidence: 99%
“…Chemical specificity is crucial in biological studies: the function of many biomolecules involves significant processing [7] and many ailments, whether hereditary, environmental, or pathological, are associated with modifications [6,8]. The attraction of imaging mass spectrometry is the ability to map the concentration profiles of specific biomolecules, recording the distributions of multiple analytes in parallel, without using a label and from native samples (such as tissue sections).…”
mentioning
confidence: 99%